Predictive value of exhaled nitric oxide and aerobic capacity for sepsis complications after liver transplantation. (17th October 2016) - Neviere, Remi; Trinh‐Duc, Pierre; Hulo, Sébastien; Edme, Jean Louis; Dehon, Aurélie; Boleslawski, Emmanuel; Dharancy, Sébastien; Lebuffe, Gilles
Summary: Our objective was to investigate the predictive value of fractional nitric oxide (NO) concentration in exhaled breath (FeNO) and aerobic capacity (peak VO2 ) for postoperative sepsis in liver transplantation candidates. Patients were identified and charts of all consecutive patients were prospectively reviewed. Bacterial sepsis represented the commonest postoperative complications (30%), which was attributed to peritonitis, pneumonia, and catheter‐related infections. Preoperative FeNO and peak VO2 values were lower in patients with postoperative sepsis. Patients with sepsis required higher needs for mechanical ventilation and ICU length of stay. Inverse correlation was found between logarithmically FeNO‐transformed data and systolic pulmonary artery pressure ( r = −0.348; P = 0.018). Multivariate analyses using bootstrap sampling method indicated that odds of sepsis were associated with lower values of peak exercise VO2 [OR = 0.790 (0.592; 0.925)] and reduced log(FeNo) [OR = 0.027 (0.001; 0.451)], but not with higher MELD scores [OR = 1.141 (0.970; 1.486)]. By evaluating the cutoff for the ROC curves in each bootstrap resampling, median and 95% confidence interval were calculated for peak VO2 : 17 [16.2; 22] ml/kg/min and FeNO: 17.2 [13.0; 33.9] ppb. We conclude that low peak exercise VO2 and reduced FeNO may help identify patients who are at risk to develop perioperative sepsis.